Edukasi Potensi Bisnis Game melalui Gamification Method bagi Generasi Z - Budiman, Diky; I Ketut Gunarsa (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
The rapid development of the global game industry has created new opportunities for digital entrepreneurship among younger generations. This community service program aims to introduce high school students to the economic potential of the game industry through the application of the gamification method. The program was conducted with students from senior high school Sedes Semarang and vocational school Pariwisata Harapan, combining interactive lectures, game-based challenges, and hands-on activities using the Scratch platform. The service-learning approach enabled students to experience a practical learning process that integrates digital literacy, creativity, and entrepreneurial insight. Throughout the program, students learned about game monetization models, basic game development logic, and the structure of simple game design. The implementation demonstrated increased student engagement, motivation, and understanding of career and business opportunities in the game sector. Students were also able to generate independent game concepts and participate actively in discussions and presentations. The results highlight that gamification is an effective method for enhancing learning outcomes and fostering digital entrepreneurial awareness among Generation Z learners. This program underscores the strategic role of higher education institutions in supporting digital competency development through participatory and innovative learning models.